Pulsar-wind-nebula-powered Galactic center X-ray filament G0.13- 0.11: Proof of the synchrotron nature by IXPE - Churazov, Eugene; Khabibullin, Ildar; Barnouin, Thibault; Bucciantini, Niccolò; Costa, Enrico; Di Gesu, Laura; Di Marco, Alessandro; Ferrazzoli, Riccardo; Forman, William; Kaaret, Philip; Kim, Dawoon E.; Kolodziejczak, Jeffery J.; et al. (EDP Sciences, 2025)
We report the discovery of X-ray polarization from the X-ray-bright filament G0.13-0.11 in the Galactic center (GC) region. This filament features a bright, hard X-ray source that is most plausibly a pulsar wind nebula (PWN) and an extended and structured diffuse component. Combining the polarization signal from IXPE with the imaging/spectroscopic data from Chandra, we find that X-ray emission of G0.13-0.11 is highly polarized PD = 57(±18)% in the 3-6 keV band, while the polarization angle is PA = 21° ± 9). This high degree of polarization proves the synchrotron origin of the X-ray emission from G0.13-0.11. In turn, the measured polarization angle implies that the X-ray emission is polarized approximately perpendicular to a sequence of nonthermal radio filaments that may be part of the GC Radio Arc. The magnetic field on the order of 100 μG appears to be preferentially ordered along the filaments. The above field strength is the fiducial value that makes our model self-consistent, while the other conclusions are largely model independent.